Legitimação social das empresas de capital aberto por meio da divulgação sobre meio ambiente natural no relato integrado - Borçato, Edileusa Cristina (2017)
The Integrated Report – IR as an instrument of voluntary disclosure of financial and non- financial information has been object of study and investigation regarding its usage and implementation by companies and its benefits. This study advances on such discussion, and, in an innovative way, explains, through discourse analysis and using the Suchman’s model, on what ways the voluntary disclosure about the natural environment have been used by open capital companies as a form of social legitimation through Integrated Reports (IR), including comparing the companies’ behavior according to its environmental impact of their operational activities. Suchman’s model considers that the managers may, strategically, through instruments of voluntary disclosure, gain, maintain, or recover the legitimacy on pragmatic, moral, or cognitive levels, employing different strategies and behavioral dynamics. The amount of 1,821 discourses about the natural environment have been analyzed, in the IR published in 2016, regarding the base year 2015, of eleven open capital companies with activities of low, medium and high environmental impacts, that participated on the BM&FBOVESPA stock market in June 2016, and declared that elaborated the reports based on the framework proposed by the International Integrated Reporting Council (IIRC). This study is categorized as qualitative, regarding the research problem; as for the objective, it is descriptive; as for the proceedings of documental data collecting, as a temporal cross- sectional perspective, since the study was carried out the period between October 2016 and June 2017. The results demonstrate that the discourse about the environment contained in the analyzed IRs have been used as ways of social legitimation by the companies in a similar manner among open capital companies with low, medium, and high environmental impacts. The predominant category employed in the discourses was to gain legitimacy in a cognitive manner, especially regarding behavioral dynamics to build reputation, formalize operations, talk naturally about the subject, and demonstrate success, and the strategies were to adapt to a model, to demands, ideals, and that protect assumptions. It can be concluded that the IRs are being used as means of management of social legitimation through voluntary disclosure of information about the natural environment, spread in different sections of the report, appearing as texts, tables, and images, with implicit and explicit strategies. These findings make it possible for report writers, shareholders, and stakeholders to understand that not all of the managers’ intentions are evident in voluntary information communication about the natural environment. For future studies, it is suggested to analyze the discourse of other capitals disclosed in the IRs; reapply this study in future periods, on the same sample, to investigate if there was any change in the way social legitimacy is sought, including procedures of intention examination, through structured interview with the IR writers; apply the study in foreign open capital companies, in order to compare behavior regarding the search for social legitimacy, in Suchman’s model.